Managing treatment-resistant schizophrenia following clozapine cessation: a case report of xanomeline–trospium and olanzapine combination therapy - Went, Nils Sumegi; Alonso, Juan D.; Rigunay, Rosemarie R.; Hershberger, Jason; You, Xiao Xiong (Frontiers in Psychiatry, 2025)
BackgroundClozapine is the gold standard for treatment-resistant schizophrenia (TRS) but is limited by rare, serious adverse events. Venous thromboembolism (VTE) and pulmonary embolism (PE) represent particularly challenging complications given their multifactorial pathophysiology, unpredictable recurrence risk, and lack of clear guidance on rechallenge.Case presentationA 44-year-old man with TRS and comorbid seizure disorder achieved over 25 years of remission on clozapine (300 mg/day). In November 2023, he developed acute deep vein thrombosis and PE, leading to permanent discontinuation despite long-term tolerability and the absence of conventional risk factors. Abrupt cessation was followed by rapid relapse. Aripiprazole, titrated to 15 mg/day, and subsequent augmentation with olanzapine failed to restore stability. A muscarinic–dopaminergic approach using xanomeline–trospium (Cobenfy™) with olanzapine was initiated, producing marked improvements in positive symptoms, affective expressivity, social engagement, and daily functioning without significant adverse effects.DiscussionMost clozapine-related VTE/PE cases necessitate discontinuation, though rare continuations under anticoagulation and multidisciplinary oversight have been described. Reviews emphasize inconclusive evidence and the need for individualized risk–benefit assessment. In this case, discontinuation was chosen collaboratively with the family, prompting exploration of alternative mechanisms.ConclusionClozapine-related VTE/PE represents a serious clinical dilemma. This case illustrates the potential of muscarinic–dopaminergic strategies to restore stability in TRS when clozapine is no longer an option.